FAKTOR-FAKTOR YANG BERPENGARUH PADA PRODUKSI HASIL LAUT DI KABUPATEN LAMONGAN - Bayu Sentosa; Sayekti Suindyah Dwiningwarni; Desy Indar Rohmawati N (HUMANIS: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2019)
This research was carried out at PT. Starfood International in Lamongan District which is located in Deandles Street, Paciran Subdistrict, is a rambling company in the field of fish processing. PT. starfood international was established in 2009. the problem formulation of this research is the factors that influence the realization of fish processing production production at PT. starfood international in increasing production. Analysis of quantitative data is a model to measure what factors affect fish processing in PT. starfood international. in this study using multiple linear regression, the results of research and discussion of problem analysis at PT. starfood international is a factor of raw materials, the selling price of production, the number of machines simultaneously or together have a significant influence on production results, this is based on the results of the F test study which shows F count is greater than F table at a significant level 0.05 ie F count (64.923)> F table value (19.00). based on the results of the study all variables affect the realization of production.